An agile supply chain analysis of Australian beef wholesalers and retailers. (1st January 2012) - Jie, Ferry; Parton, Kevin A.; Cox, Rodney J.
The objective of this research was to develop a method to judge the extent of agility in the supply chain management of the Australian beef wholesale and retail sector. Based on the responses to a survey of managers, regression analysis was used to develop a model linking management actions to supply chain practices and competitive advantage. The strongest and most consistent relationships observed were from commitment and trust, information quality and strategic supplier partnerships to competitive advantage. Although commitment and trust were seen to support agile supply chain management, information quality and strategic supplier partnerships were more related to developing food quality in an industry where customer relationships are important. Agility of Australian beef supply chains can be improved through, for example, enhanced communication between retailers and their suppliers and better internal teamwork in retail firms. There has been virtually no previous research on the performance of Australian beef supply chains. The paper is an attempt to fill this gap. Also the methods are innovative and could be applied to similar agribusiness supply chains in other countries.